(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
In this contribution, new data concerning lichen-forming and lichenicolous fungi in Ukraine are presented. It includes new records, exclusions, and confirmations to the Ukrainian administrative regions of taxa in the genera of Absconditella, Alyxoria, Arthonia, Athelia, Briancoppinsia, Buellia, Buelliella, Caloplaca, Candelariella, Chaenotheca, Circinaria, Clypeococcum, Didymocyrtis, Diplotomma, Hypocenomyce, Lawalreea, Lecania, Lecidea, Lichenochora, Lichenoconium, Lichenostigma, Micarea, Monodictys, Mycomicrothelia, Muellerella, Naevia, Pachyphiale, Parmeliopsis, Pertusaria, Phaeophyscia, Phoma, Physcia, Physconia, Piccolia, Placynthiella, Polycoccum, Polyozosia, Porpidia, Pronectria, Protoparmeliopsis, Pseudoschismatomma, Punctelia, Ramalina, Rinodina, Sarcopyrenia, Sclerophora, Sphaerellothecium, Staurothele, Strangospora, Stigmidium, Taeniolella, Tephromela, Thelocarpon, Tuckermannopsis, Verrucaria, Xanthoparmelia, Xanthoria, Zeroviella. Among them 24 species of lichen-forming and lichenicolous fungi are new to the Kharkiv region, 13 species new to the Rivne region, 9 species new to the Mykolaiv region, 6 species new to the Kherson region, 3 species new to the Zaporizhzhia region, 3 species new to the Ivano-Frankivsk region, 3 species new to the Ternopil region, 2 species new to the Dnipropetrovsk and Zakarpattia, Chernivtsi and Volyn regions, one species new to the Chernihiv, Khmelnytskyi, Kyiv, Poltava, Sumy regions as well as 5 species new to Autonomous Republic of Crimea.